Enterprise Data Integration a critical piece of a service-oriented architecture. - Chong, Ivan
A large company found itself handicapped by an ornery snarl of siloed applications that compromised its agility, performance and profitability. Its IT department was constantly behind schedule and over budget in hand coding point to point connectivity among supply chain, financials, CRM, and other packaged and custom-built legacy applications.